Carbon Dioxide Activation and Reaction Induced by Electron Transfer at an Oxide–Metal Interface1. Issue 42 (26th May 2015) - Calaza, Florencia; Stiehler, Christian; Fujimori, Yuichi; Sterrer, Martin; Beeg, Sebastian; Ruiz‐Oses, Miguel; Nilius, Niklas; Heyde, Markus; Parviainen, Teemu; Honkala, Karoliina; Häkkinen, Hannu; Freund, Hans‐Joachim
Abstract A model system has been created to shuttle electrons through a metal–insulator–metal (MIM) structure to induce the formation of a CO2 anion radical from adsorbed gas‐phase carbon dioxide that subsequently reacts to form an oxalate species. The process is completely reversible, and thus allows the elementary steps involved to be studied at the atomic level. The oxalate species at the MIM interface have been identified locally by scanning tunneling microscopy, chemically by IR spectroscopy, and their formation verified by density functional calculations.